2016
DOI: 10.1002/anie.201603260
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming the Limitations of C−H Activation with Strongly Coordinating N‐Heterocycles by Cobalt Catalysis

Abstract: Strongly coordinating nitrogen heterocycles, including pyrimidines, oxazolines, pyrazoles, and pyridines, were fully tolerated in cobalt-catalyzed C-H amidations by imidate assistance. Structurally complex quinazolines are thus accessible in a step-economic manner. Our findings also establish the relative powers of directing groups in cobalt(III)-catalyzed C-H functionalization for the first time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
59
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(64 citation statements)
references
References 124 publications
4
59
0
1
Order By: Relevance
“…[1] Furthermore, it would also provide new retrosynthetic approaches for the synthesis of complex natural products and late-stage derivatization of bioactive compounds. [2] In spite of the dramatic impact on synthetic chemistry, most of the CÀH functionalization protocols still involve the use of precious and rare transition metal catalysts, such as Rh, [3] Ir, [4] Pd, [5] and Ru, [6] which are not ideal due to the stringent environmental and economic requirements nowadays. Thus, our group along with others has focused on using earth-abundant cobalt catalysts for such CÀH bond activations by taking advantages of their unique merits, including high catalytic efficiency, inexpensive access, and low toxicity.…”
mentioning
confidence: 99%
“…[1] Furthermore, it would also provide new retrosynthetic approaches for the synthesis of complex natural products and late-stage derivatization of bioactive compounds. [2] In spite of the dramatic impact on synthetic chemistry, most of the CÀH functionalization protocols still involve the use of precious and rare transition metal catalysts, such as Rh, [3] Ir, [4] Pd, [5] and Ru, [6] which are not ideal due to the stringent environmental and economic requirements nowadays. Thus, our group along with others has focused on using earth-abundant cobalt catalysts for such CÀH bond activations by taking advantages of their unique merits, including high catalytic efficiency, inexpensive access, and low toxicity.…”
mentioning
confidence: 99%
“…Later, Ackermann et al. published the synthesis of quinazoline moiety by the coupling of benzimidates 49 with dioxazolones 47 (Scheme ) . Other strongly coordinating directing groups such as pyrazole, pyridine, oxazole, and pyrimidine were installed in the benzimidate substrate and tested for its selectivity.…”
Section: Cocp* Catalyzed Annulation Reactionsmentioning
confidence: 99%
“…Other heterocyclic ring systems being synthesized using Cp*Co III catalysis include quinolines, [133a, 140] 1H-indazoles, [141] pyrroles, [142] quinazolines, [143] indolizines, [144] pyrido[2',1':2,3]pyrimido[1,6-a]indol-5-iums, [145] and2 H-chromenes. [146] In Scheme 35 it was already shown that the reactionw ith alkynes can lead to alkenylation in position-2 of indole.…”
Section: Scheme27 Aminoquinoline As Powerfuldgi Nc (Sp 3 )àHa Ctivatmentioning
confidence: 99%